Lipiodol retention pattern after TACE for HCC is a predictor for local progression in lesions with complete response - Marco Dioguardi Burgio; Riccardo Sartoris; Claudia Libotean; Magaly Zappa; Annie Sibert; Valérie Vilgrain; Maxime Ronot (Cancer Imaging, 2019)
Abstract Background To evaluate the predictive value of the lipiodol retention pattern for local progression of HCC with a complete response (CR) on CT according to mRECIST criteria after a first session of conventional chemoembolization (cTACE). Methods From January 2014 to May 2016 all consecutive patients undergoing a first cTACE session for HCC were identified. Inclusion criteria were the presence of ≤3 HCCs and available pre- and post-cTACE CT. Tumor response was classified according to mRECIST criteria. The analysis focused on tumors with a CR. The lipiodol retention pattern in these tumors was classified as complete (C-Lip, covering the entire tumor volume), or incomplete (I-Lip). Local progression was defined as the reappearance of areas of enhancement on arterial-phase images with washout on portal/delayed phase images within 2 cm from treated tumors on follow-up CT. Results The final population included 50 patients with 82 HCCs. A total of 46 (56%) HCCs were classified with a CR, including 16 (35%) with I-Lip, and 30 (65%) with C-Lip. After a median follow-up of 14 months (3.2–35.9 months), 15/16 (94%) and 10/30 (30%) of I-Lip and C-Lip HCCs showed local progression on CT, respectively (p < 0.001), with no significant difference in the time to progression (mean 11.1 ± 2 vs. 13.4 ± 3 months for I-Lip and C-Lip, respectively p = 0.51). Conclusions HCCs with incomplete lipiodol retention after a first cTACE session have a high risk of local progression even when there is a CR according to mRECIST, and should be considered to be incompletely treated.